Blood flow study in a stenosed carotid bifurcation - Luísa Costa Sousa (2013)
The goal of this work is the use of anatomically realistic blood flow simulations by the finite element method derived from in vivo medical imaging to obtain patient-specific flow phenomena associated with the atherosclerosis disease. A good agreement between ultrasound imaging data and computational simulated results was achieved.